Ballads - Stevenson, Robert Louis, 1850-1894 (Floating Press, 2008)
Robert Louis Stevenson (1850 - 1894) is most famous for his novels Treasure Island and The Strange Case of Dr. Jekyll and Mr. Hyde . His book of ballads draws on the traditional stories of his native Scotland as well as on the fantastical places of his imagination. Stevenson was a great traveler, living out the last years of his life in the Pacific. He was admired by many of his fellow novelists but contemporary critics counted his popularity against his literary talent...